2007
DOI: 10.1111/j.1745-7599.2007.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of HIV disclosure: Disclosure and types of social relationships

Abstract: Results of this study provide a "Model of HIV Disclosure" that can be utilized by nurse practitioners and other HCPs in clinical practice when providing treatment, counseling, and prevention education for HIV+ clients and for prevention education for HIV negative clients--especially for family, friends, sexual partners, and employers of HIV+ clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 20 publications
8
64
0
Order By: Relevance
“…These patterns of association suggest that differences in disclosure target and intention may partly explain the previous inconsistent results on disclosure, stigma and social support (Chaudoir et al, 2011;Smith et al, 2008). It confirms previous findings that stigma and social support may play different roles in disclosure decisions to partners, family, friends or broader community (Bairan et al, 2007;Derlega et al, 2002), and that consequences may differ when disclosing to different types of actors (Greeff et al, 2008;Norman et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These patterns of association suggest that differences in disclosure target and intention may partly explain the previous inconsistent results on disclosure, stigma and social support (Chaudoir et al, 2011;Smith et al, 2008). It confirms previous findings that stigma and social support may play different roles in disclosure decisions to partners, family, friends or broader community (Bairan et al, 2007;Derlega et al, 2002), and that consequences may differ when disclosing to different types of actors (Greeff et al, 2008;Norman et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Several reviewers highlighted the need for improved measurement (e.g. Obermeyer et al, 2011;Smith et al, 2008), and several authors proposed models to guide research on disclosure (Bairan et al, 2007;Bird & Voisin, 2011;Chaudoir & Fisher, 2010;Chaudoir et al, 2011;Mayfield Arnold et al, 2008;Serovich et al, 2008) and stigma (Bos et al, 2013;Earnshaw & Chaudoir, 2009;Mahajan et al, 2008). However, although most research has focused on the broader process of increasing one's disclosure levels from none or few confidants to the entire social network, the existing theoretical models interpreted all empirical evidence in terms of causes and consequences of single disclosure events.…”
Section: Introductionmentioning
confidence: 99%
“…Shame is one psychological experience an individual may have as a result of internalized stigma, and several studies in the literature have demonstrated these constructs to be separate, but related (Cunningham et al, 2002;Duffy, 2005;Fortenberry et al, 2002). Studies of HIV-positive adults living in the US have also demonstrated that stigma is associated with poor social support and depressive symptoms (Bairan et al, 2007;Carr and Gramling, 2004;Sowell et al, 1997;Vanable et al, 2006). Thus, we hypothesized internalized stigma would also be moderately negatively correlated (r= −0.3 to −0.5) with social support and mental health.…”
Section: Content and Construct Validity Of Stigma Measurementioning
confidence: 94%
“…According to this model, these two together inform a determined 'disclosure rule' (or more simply, a disclosure decision) i.e. tell my friends (Arnold et al, 2008)' Bairan and colleagues [15] provide a model of HIV disclosure that describes when disclosure is likely to occur/ not occur, as a function of the relationship context (whether the relationship is sexual or non-sexual). According to this model, disclosure within a sexual relationship is likely to occur when the relationship is committed and long term and is significantly less likely to occur when the sexual relationship is casual and short term.…”
Section: Introductionmentioning
confidence: 99%